Resin laminate, dielectric layer, resin-coated metal foil, capacitor element, and capacitor-embedded printed wiring board

JP7645822B2Active Publication Date: 2025-03-14MITSUI MINING & SMELTING CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021574653
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-28
Filing Date
2021-01-19
Publication Date
2025-03-14
Estimated Expiration
2041-01-19

Smart Images

  • Figure 0007645822000003
    Figure 0007645822000003
  • Figure 0007645822000004
    Figure 0007645822000004
  • Figure 0007645822000005
    Figure 0007645822000005
Patent Text Reader

Abstract

Provided is a resin layered product that when used as a dielectric layer of a capacitor, can ensure good circuit adhesion, voltage resistance, and interlayer insulation reliability while having improved dielectric characteristics. The resin layered product comprises a first layer made of a first resin composition, and a second layer made of a second resin composition. The first resin composition contains a resin component including an epoxy resin, a diamine compound, and a polyimide resin, and 60-85 parts by weight of a composite metal oxide including at least two selected from Ba, Ti, and the like with respect to 100 parts by weight of the solid content of the first resin composition. The contained amount of the polyimide resin is 20-60 parts by weight with respect to 100 parts by weight of the resin component. The second resin composition contains a resin component including an epoxy resin and a diamine compound but not including a polyimide resin, and 70-90 parts by weight of a composite metal oxide including at least two selected from Ba, Ti, and the like with respect to 100 parts by weight of the solid content of the second resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin laminate, a dielectric layer, a resin-coated metal foil, a capacitor element, and a printed wiring board with a built-in capacitor. [Background technology]

[0002] Resin compositions for capacitor-embedded printed wiring boards are known as resin compositions used in the manufacture of copper-clad laminates and printed wiring boards. Such resin compositions function as a dielectric layer in a capacitor when cured. For example, Patent Document 1 (WO2019 / 150994A1) discloses a resin composition comprising a resin component containing an epoxy resin, a diamine compound, and a polyimide resin, and a dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi, in an amount of 60 parts by weight to 85 parts by weight per 100 parts by weight of the solid content of the resin composition. This document describes that when the resin composition is used as a dielectric layer of a capacitor, it is possible to suppress a decrease in capacitance or a decrease in dielectric constant at high temperatures while ensuring excellent dielectric properties and circuit adhesion.

[0003] Also, a capacitor using a resin laminate having a plurality of resin composition layers as a dielectric layer is known. For example, Patent Document 2 (JP Patent Publication No. 2003-039595) discloses a double-sided copper-clad laminate for forming a capacitor layer, which comprises a resin layer serving as a dielectric and copper foil layers serving as conductors provided on both sides of the resin layer, and the resin layer has a three-layer structure of a thermosetting resin layer / heat-resistant film layer / thermosetting resin layer, and the heat-resistant film layer has a Young's modulus of 300 kg / mm 2 Above, tensile strength 20kg / mm 2It is said to have normal characteristics of tensile elongation of 5% or more. This double-sided copper-clad laminate is said to be able to reliably prevent discharge between the roughened areas of the copper foils facing each other when a high voltage of 500V or more is applied between the copper foil surfaces. Furthermore, Patent Document 3 (JP 2006-165400 A) describes a method for producing a capacitor layer-forming material for forming a capacitor layer of a printed wiring board having conductive layers positioned on the outer layers of both sides and a dielectric layer having a three-layer structure of a thermosetting polymer layer / polymerization reaction layer / thermosetting polymer layer sandwiched between the conductive layers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] WO2019 / 150994A1 [Patent Document 2] JP 2003-039595 A [Patent Document 3] JP 2006-165400 A Summary of the Invention

[0005] Incidentally, printed wiring boards are widely used in electronic communication devices such as portable electronic devices. In particular, with the recent trend toward lighter, thinner, shorter, smaller, and more highly functional portable electronic communication devices, reducing noise in printed wiring boards has become an issue. Capacitors are important for noise reduction, but in order to achieve high performance, it is desirable for such capacitors to be small and thin enough to be incorporated into the inner layer of a printed wiring board. In this regard, although the dielectric layer made of the resin composition disclosed in Patent Document 1 (WO2019 / 150994A1) provides good performance to a certain extent, further improvement in capacitance is desired. On the other hand, it is also desirable to ensure the adhesion between the resin layer and the circuit (i.e., circuit adhesion), voltage resistance, and interlayer insulation reliability.

[0006] The present inventors have now discovered that by using a resin laminate comprising a first layer composed of a specified first resin composition and a second layer composed of a specified second resin composition as a dielectric layer of a capacitor, it is possible to ensure good circuit adhesion, voltage resistance and interlayer insulation reliability while improving dielectric properties such as capacitance.

[0007] Therefore, an object of the present invention is to provide a resin laminate which, when used as a dielectric layer of a capacitor, can ensure good circuit adhesion, voltage resistance and interlayer insulation reliability while improving dielectric properties.

[0008] According to one aspect of the present invention, there is provided a resin laminate comprising a first layer made of a first resin composition and a second layer made of a second resin composition provided on one surface of the first layer, The first resin composition is A resin component including an epoxy resin, a diamine compound, and a polyimide resin; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 60 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the solid content of the first resin composition; a content of the polyimide resin in the first resin composition is 20 parts by weight or more and 60 parts by weight or less with respect to 100 parts by weight of the resin component; The second resin composition is a resin component containing an epoxy resin and a diamine compound but not containing a polyimide resin; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 70 parts by weight or more and 90 parts by weight or less relative to 100 parts by weight of the solid content of the second resin composition; A resin laminate comprising the above is provided.

[0009] According to another aspect of the present invention, there is provided a dielectric layer including the resin laminate, in which the first resin composition and the second resin composition are cured.

[0010] According to another aspect of the present invention, there is provided a resin-coated metal foil comprising a metal foil and the resin laminate provided on at least one surface of the metal foil.

[0011] According to another aspect of the present invention, there is provided a capacitor element having the above-described dielectric layer.

[0012] According to another aspect of the present invention, there is provided a printed wiring board with an embedded capacitor, comprising the above-described dielectric layer. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic cross-sectional view showing an example of a resin laminate according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the resin laminate according to the present invention. [Diagram 3] FIG. 2 is a diagram showing an example of a manufacturing process of the resin laminate and the resin-coated metal foil shown in FIG. [Figure 4] 3 is a diagram showing another example of the manufacturing process of the resin laminate and the resin-coated metal foil shown in FIG. [Diagram 5] FIG. 3 is a diagram showing an example of a manufacturing process of the resin laminate and the resin-coated metal foil shown in FIG. 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Resin laminate FIG. 1 shows a schematic diagram of a resin laminate 10 of the present invention. The resin laminate 10 includes a first layer 12 and a second layer 14 provided on one surface of the first layer 12. The first layer 12 is composed of a first resin composition. The first resin composition includes a resin component and a dielectric filler. The resin component includes an epoxy resin, a diamine compound, and a polyimide resin. The dielectric filler of the first resin composition is a composite metal oxide including at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi, and is included in the first resin composition in an amount of 60 parts by weight or more and 85 parts by weight or less with respect to 100 parts by weight of the solid content of the first resin composition. The content of the polyimide resin in the first resin composition is 20 parts by weight or more and 60 parts by weight or less with respect to 100 parts by weight of the resin component. On the other hand, the second layer 14 is composed of a second resin composition. The second resin composition includes a resin component and a dielectric filler. The resin component includes an epoxy resin and a diamine compound, but does not include a polyimide resin. The dielectric filler of the second resin composition is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, and is contained in the second resin composition in an amount of 70 parts by weight to 90 parts by weight based on 100 parts by weight of the solid content of the second resin composition. In this way, by using the resin laminate 10 having the first layer 12 composed of a predetermined first resin composition and the second layer 14 composed of a predetermined second resin composition as the dielectric layer of a capacitor, it is possible to ensure good circuit adhesion, voltage resistance and interlayer insulation reliability while improving dielectric properties such as capacitance.

[0015] As mentioned above, although the dielectric layer made of the resin composition disclosed in Patent Document 1 provides a certain degree of good performance, further improvement of the capacitance is desired. In this regard, although the capacitance can be improved by increasing the content of the dielectric filler in the resin composition, the increase in the dielectric filler reduces the adhesion between the resin layer and the circuit (i.e., circuit adhesion). For this reason, how to balance dielectric properties such as capacitance and circuit adhesion becomes an issue. In addition, it is also desired that the resin composition ensures voltage resistance and interlayer insulation reliability when used as a dielectric layer of a capacitor. These problems are conveniently solved by the resin laminate 10 of the present invention. In particular, in the resin laminate 10 of the present invention, the first resin composition constituting the first layer 12 is particularly excellent in circuit adhesion, while the second resin composition constituting the second layer 14 is particularly excellent in dielectric properties, so that the dielectric properties such as capacitance and circuit adhesion, which tend to be in a trade-off relationship by nature, can be conveniently combined.

[0016] Therefore, the first layer 12 can be thinner as long as it satisfies the desired circuit adhesion, and at the same time, the second layer 14 having excellent dielectric properties can be made as thick as possible to realize a higher capacitance as a resin laminate. For example, the thickness of the first layer 12 is preferably 0.5% to 100% of the thickness of the second layer 14, more preferably 15% to 100%, even more preferably 25% to 75%, and particularly preferably 35% to 50%. However, the first layer 12 may be thicker than the second layer 14 as long as the desired properties are obtained. From the viewpoint of circuit adhesion, the thickness of the first layer 12 is preferably 0.1 μm to 5 μm, more preferably 0.1 μm to 3 μm, particularly preferably 0.1 μm to 2 μm, and most preferably 0.5 μm to 2 μm. From the viewpoint of ensuring a high electrostatic capacitance, the thickness of the second layer 14 is preferably 0.1 μm or more and 25 μm or less, more preferably 0.4 μm or more and 17 μm or less, particularly preferably 0.9 μm or more and 8 μm or less, and most preferably 1 μm or more and 4 μm or less.

[0017] The resin laminate 10 may have any layer structure as long as it includes a first layer 12 and a second layer 14. According to a preferred embodiment of the present invention, the resin laminate 10 may have a two-layer structure including a first layer 12 and a second layer 14 as shown in FIG. 1. Alternatively, the resin laminate 10 may have a three-layer structure like the resin laminate 10' shown in FIG. 2. That is, according to another preferred embodiment of the present invention, the resin laminate 10' may further include another first layer 12 composed of a first resin composition on the surface of the second layer 14 away from the first layer 12. By adopting such a three-layer structure of the first layer 12 / second layer 14 / first layer 12, improved circuit adhesion can be realized on both surfaces of the resin laminate 10.

[0018] The first resin composition constituting the first layer 12 contains a resin component and a dielectric filler. The resin component contains an epoxy resin, a diamine compound, and a polyimide resin. The first resin composition contributes to all of the dielectric characteristics, circuit adhesion, voltage resistance, and interlayer insulation reliability, but is particularly excellent in circuit adhesion. The first resin composition or the first layer 12 may further contain any other components as long as the desired functions are not impaired.

[0019] The epoxy resin used in the first resin composition is not particularly limited as long as it has two or more epoxy groups in the molecule and can be used for electrical and electronic material applications. The preferred content of the epoxy resin in the first resin composition is 15 parts by weight or more and 80 parts by weight or less, more preferably 40 parts by weight or more and 65 parts by weight or less, and even more preferably 45 parts by weight or more and 60 parts by weight or less, relative to 100 parts by weight of the resin component. Examples of the epoxy resin in the first resin composition include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, biphenyl novolac type epoxy resin, cresol novolac type epoxy resin, alicyclic epoxy resin, glycidylamine type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, dicyclopentadiene type epoxy resin, and any combination thereof. From the viewpoint of maintaining the heat resistance of the cured product, aromatic epoxy resins or polyfunctional epoxy resins are preferred, and bisphenol A type epoxy resins, phenol novolac type epoxy resins, naphthalene type epoxy resins, cresol novolac type epoxy resins, or biphenyl novolac type epoxy resins are more preferred.

[0020] The diamine compound used in the first resin composition is not particularly limited as long as it functions as a curing agent for the epoxy resin, has two amino groups in the molecule, and can be used for electrical and electronic materials. The preferred content of the diamine compound in the first resin composition is an amount in which the number of active hydrogen groups of the diamine compound is 0.5 to 1.5, more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.5 to 1.0, and even more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.65 to 1.0, when the number of epoxy groups of the epoxy resin is 1. Here, the "number of epoxy groups of the epoxy resin" is a value obtained by dividing the solid content mass of the epoxy resin present in the resin component by the epoxy equivalent. In addition, the "number of active hydrogen groups of the diamine compound" is a value obtained by dividing the solid content mass of the diamine compound present in the resin component by the active hydrogen group equivalent. Examples of the diamine compound include 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ether, 1,4- Examples thereof include bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(aminomethyl)cyclohexane, and any combination thereof, and preferably 4,4'-diaminodiphenyl sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

[0021] In the first resin composition, the total content of the epoxy resin and the diamine compound is preferably 40 parts by weight or more and 80 parts by weight or less, more preferably 50 parts by weight or more and 80 parts by weight or less, further preferably 50 parts by weight or more and 70 parts by weight or less, and particularly preferably 60 parts by weight or more and 70 parts by weight or less, relative to 100 parts by weight of the resin component. With such a content, circuit adhesion and heat resistance can be improved.

[0022] The polyimide resin used in the first resin composition contributes not only to reducing the dielectric loss tangent but also to improving the circuit adhesion. The content of the polyimide resin in the first resin composition is 20 parts by weight or more and 60 parts by weight or less, preferably 20 parts by weight or more and 50 parts by weight or less, more preferably 30 parts by weight or more and 50 parts by weight or less, and even more preferably 30 parts by weight or more and 40 parts by weight or less, relative to 100 parts by weight of the resin component. With such a content, excellent dielectric properties and circuit adhesion can be exhibited while ensuring good heat resistance. The polyimide resin is not particularly limited as long as it can realize the desired dielectric properties, circuit adhesion and heat resistance, but a polyimide resin soluble in an organic solvent (hereinafter referred to as an organic solvent-soluble polyimide) is preferable from the viewpoint of forming a varnish and a coating film that are well compatible with the epoxy resin. The organic solvent in which the polyimide resin is soluble is preferably one having a solubility parameter (SP value) of 7.0 or more and 17.0 or less, and preferred examples of such organic solvents include methyl ethyl ketone, toluene, xylene, N-methylpyrrolidone, dimethylacetamide, dimethylformamide, cyclopentanone, cyclohexanone, cyclohexane, methylcyclohexane, ethylene glycol, ethylene glycol dimethyl ether, ethylene glycol acetate, and any combination thereof. In particular, those having at least one functional group capable of reacting with an epoxy group at the molecular end are preferred in terms of maintaining heat resistance after curing. Specifically, the polyimide resin preferably has at least one functional group selected from the group consisting of a carboxyl group, a sulfonic acid group, a thiol group, and a phenolic hydroxyl group as a functional group at its end or side chain. By having such a functional group, the heat resistance of the polyimide resin is maintained while the solubility in organic solvents and the compatibility with epoxy resins are improved. Among these, it is more preferred to use a polyimide resin having a carboxyl group as a functional group at its end or side chain.

[0023] A preferred organic solvent-soluble polyimide is one obtained by imidizing a tetracarboxylic dianhydride with a diamine compound. Examples of tetracarboxylic dianhydrides include 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenyl)phenyl]propane dianhydride, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzoxazole dianhydride, 2,2',3,3'-biphenyltetracarboxylic ... Examples of such anhydride include dibenzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 2,3,5,6-pyridine tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, and the like, or compounds having alkyl or halogen atom substituents on these aromatic rings, and any combinations thereof. Among these, from the viewpoint of improving the heat resistance of the resin composition, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenyl)phenyl]propane dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, or a polyimide resin mainly composed of 2,2',3,3'-biphenyltetracarboxylic dianhydride is preferred. On the other hand, examples of the diamine compound include those mentioned above.

[0024] The dielectric filler used in the first resin composition is a component that provides a desired high capacitance to the resin laminate as the dielectric layer, and is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi. Preferred examples of the composite metal oxide include particles containing at least one selected from the group consisting of BaTiO3, SrTiO3, Pb(Zr,Ti)O3, PbLaTiO3, PbLaZrO, and SrBi2Ta2O9, which have high capacitance and can be mixed into the first resin composition, and more preferably BaTiO3. Note that Pb(Zr,Ti)O3 means Pb(Zr x Ti 1-x )O3 (where 0 ≦ x ≦ 1, typically 0 < x < 1). The content of the dielectric filler in the first resin composition is 60 parts by weight or more and 85 parts by weight or less, preferably 70 parts by weight or more and 85 parts by weight or less, and more preferably 75 parts by weight or more and 85 parts by weight or less, based on 100 parts by weight of the solid content of the first resin composition. Also, although the particle size of the dielectric filler is not particularly limited, from the viewpoint of maintaining the adhesion between the resin composition and the metal foil, the average particle size D 50 measured by laser diffraction scattering particle size distribution measurement is preferably 0.01 μm or more and 2.0 μm or less, more preferably 0.05 μm or more and 1.0 μm or less, and even more preferably 0.1 μm or more and 0.5 μm or less.

[0025] The second resin composition constituting the second layer 14 contains a resin component and a dielectric filler. This resin component contains an epoxy resin and a diamine compound but does not contain a polyimide resin. The second resin composition contributes to all of the dielectric properties, circuit adhesion, voltage resistance, and interlayer insulation reliability, and is particularly excellent in dielectric properties (capacitance). The second resin composition or the second layer 14 may further contain any other component (except polyimide resin) as long as the desired functions are not impaired.

[0026] The epoxy resin used in the second resin composition is not particularly limited as long as it has two or more epoxy groups in the molecule and can be used for electrical and electronic material applications. The preferred content of the epoxy resin in the second resin composition is 15 parts by weight or more and 85 parts by weight or less, more preferably 25 parts by weight or more and 80 parts by weight or less, and even more preferably 35 parts by weight or more and 75 parts by weight or less, relative to 100 parts by weight of the resin component. Examples of the epoxy resin in the second resin composition include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, phenol novolac type epoxy resin, biphenyl novolac type epoxy resin, cresol novolac type epoxy resin, alicyclic epoxy resin, glycidylamine type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, dicyclopentadiene type epoxy resin, and any combination thereof. From the viewpoint of maintaining the heat resistance of the cured product, aromatic epoxy resins or polyfunctional epoxy resins are preferred, and bisphenol A type epoxy resins, phenol novolac type epoxy resins, naphthalene type epoxy resins, cresol novolac type epoxy resins, or biphenyl novolac type epoxy resins are more preferred.

[0027] The diamine compound used in the second resin composition is not particularly limited as long as it functions as a curing agent for the epoxy resin, has two amino groups in the molecule, and can be used for electrical and electronic materials. The preferred content of the diamine compound in the second resin composition is an amount in which the number of active hydrogen groups of the diamine compound is 0.5 to 1.5, more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.5 to 1.0, and even more preferably an amount in which the number of active hydrogen groups of the diamine compound is 0.65 to 1.0, when the number of epoxy groups of the epoxy resin is 1. Here, the "number of epoxy groups of the epoxy resin" is a value obtained by dividing the solid content mass of the epoxy resin present in the resin component by the epoxy equivalent. In addition, the "number of active hydrogen groups of the diamine compound" is a value obtained by dividing the solid content mass of the diamine compound present in the resin component by the active hydrogen group equivalent. Examples of the diamine compound include 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ether, 1,4- Examples thereof include bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis(aminomethyl)cyclohexane, and any combination thereof, and preferably 4,4'-diaminodiphenyl sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, and 2,2-bis[4-(4-aminophenoxy)phenyl]propane.

[0028] In the second resin composition, the total content of the epoxy resin and the diamine compound is preferably 100 parts by weight with respect to 100 parts by weight of the resin component. Since the second resin composition does not contain a polyimide resin, unlike the first resin composition, the resin component is typically composed of two components, an epoxy resin and a diamine compound.

[0029] The dielectric filler used in the second resin composition is a component that provides a desired high capacitance to the resin laminate, and is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta, and Bi. Preferred examples of the composite metal oxide include particles containing at least one selected from the group consisting of BaTiO3, SrTiO3, Pb(Zr,Ti)O3, PbLaTiO3, PbLaZrO, and SrBi2Ta2O9, which have a high capacitance and can be mixed into the second resin composition, and more preferably BaTiO3. Note that Pb(Zr,Ti)O3 means Pb(Zr x Ti 1-x )O3 (where 0 ≦ x ≦ 1, typically 0 < x < 1). The content of the dielectric filler in the second resin composition is 70 parts by weight or more and 90 parts by weight or less, preferably 75 parts by weight or more and 90 parts by weight or less, more preferably 80 parts by weight or more and 90 parts by weight or less, with respect to 100 parts by weight of the solid content of the second resin composition. Also, the particle size of the dielectric filler is not particularly limited, but from the viewpoint of maintaining the adhesion between the resin composition and the metal foil, the average particle size D 50 measured by laser diffraction scattering particle size distribution measurement is preferably 0.01 μm or more and 2.0 μm or less, more preferably 0.05 μm or more and 1.0 μm or less, and even more preferably 0.1 μm or more and 0.5 μm or less.

[0030] The first resin composition and / or the second resin composition may further contain a filler dispersant. By further containing a filler dispersant, the dispersibility of the dielectric filler can be improved when the resin varnish and the dielectric filler are kneaded. The filler dispersant may be any known dispersant that can be used as appropriate, and is not particularly limited. Examples of preferred filler dispersants include ionic dispersants such as phosphonic acid type, cationic type, carboxylic acid type, and anionic type dispersants, as well as nonionic dispersants such as ether type, ester type, sorbitan ester type, diester type, monoglyceride type, ethylene oxide addition type, ethylenediamine base type, and phenol type dispersants. Other examples include coupling agents such as silane coupling agents, titanate coupling agents, and aluminate coupling agents.

[0031] A curing accelerator may be added to the first resin composition and / or the second resin composition to accelerate the curing of the resin components. Preferable examples of the curing accelerator include imidazole-based and amine-based curing accelerators. From the viewpoint of storage stability and curing efficiency of the resin composition, the content of the curing accelerator is preferably 0.01 parts by weight or more and 3 parts by weight or less, more preferably 0.1 parts by weight or more and 2 parts by weight or less, relative to 100 parts by weight of the non-volatile components in the resin composition.

[0032] The imidazole-based curing accelerator is incorporated into the molecular structure as part of the epoxy resin without being liberated as an ion after the curing reaction with the epoxy resin, and therefore can provide the resin layer with excellent dielectric properties and insulation reliability. The content of the imidazole-based curing accelerator is not particularly limited, and may be appropriately determined as an amount that provides desired curing while taking into account various conditions such as the composition of the resin layer. Examples of imidazole hardening accelerators include 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole. Imidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and any combination thereof.Preferred examples of the imidazole-based hardening accelerator include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole. Among these, 2-phenyl-4-methylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole, which are imidazole-based hardening accelerators having a phenyl group, are more preferred from the viewpoint of chemical stability in the semi-cured (B stage) state of the resin layer. Among these, 2-phenyl-4-methyl-5-hydroxymethylimidazole is particularly preferred.

[0033] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, and any combination thereof.

[0034] Resin-coated metal foil The resin laminate of the present invention is preferably used as a resin for a resin-coated metal foil. By forming the resin-coated metal foil in advance, it is possible to efficiently manufacture a capacitor element or a capacitor-embedded printed wiring board without separately forming a resin laminate or a dielectric layer. That is, according to a preferred embodiment of the present invention, a resin-coated metal foil is provided, which includes a metal foil and a resin laminate provided on at least one side of the metal foil. In addition, the resin-coated metal foil may be one in which the metal foil is provided on both sides of the resin laminate, and this configuration can correspond to a metal-clad laminate. Typically, the resin laminate is in the form of a resin layer, and the first resin composition and / or the second resin composition constituting the resin laminate are applied to a metal foil using a gravure coating method so that the thickness of the resin layer after drying is a predetermined value, and then dried to obtain a resin-coated metal foil. The coating method is arbitrary, but in addition to the gravure coating method, a die coating method, a knife coating method, etc. can be adopted. In addition, it is also possible to coat using a doctor blade, a bar coater, etc.

[0035] The lamination of the first layer 12 and the second layer 14 may be performed by any method, and is not particularly limited. For example, as shown in FIG. 3, the first resin composition may be applied to a metal foil 16 to form the first layer 12 to obtain a first resin-coated metal foil 20, while the second resin composition may be applied to another metal foil 16' to form the second layer 14 to obtain a second resin-coated metal foil 22, and these may be laminated together so that the first layer 12 and the second layer 14 face each other. Alternatively, as shown in FIG. 4, the first resin composition may be applied to the metal foil 16 to form the first layer 12, and then the second resin composition may be applied on the first layer 12 to form the second layer 14 to obtain a two-layer resin-coated metal foil 24. In this case, a metal-clad laminate 30 can be obtained by laminating another metal foil 16' on the second layer 14. Alternatively, in the case of a three-layer resin laminate, it is preferable to laminate a first resin-coated metal foil 20 having a first layer 12 formed on a metal foil 16 to a two-layer resin-coated metal foil 24' having a first layer 12 and a second layer 14 formed on another metal foil 16', so that the first layer 12 faces the second layer 14, as shown in Fig. 5. From the viewpoint of forming a resin laminate or a dielectric layer by laminating them facing each other in this manner, it is preferable that the first resin composition and the second resin composition are semi-cured when laminated.

[0036] The metal foil is preferably a copper foil. The metal foil such as copper foil may be a metal foil (so-called raw foil) that is electrolytically or rolled, or may be in the form of a surface-treated foil that has been surface-treated on at least one side. The surface treatment may be any of various surface treatments performed to improve or impart certain properties (e.g., rust resistance, moisture resistance, chemical resistance, acid resistance, heat resistance, and adhesion to a substrate) to the surface of the metal foil. The surface treatment may be performed on at least one side of the metal foil, or on both sides of the metal foil. Examples of surface treatments performed on the metal foil include rust prevention treatment, silane treatment, roughening treatment, and barrier formation treatment.

[0037] The ten-point average roughness Rzjis of the surface of the metal foil facing the resin laminate, measured according to JIS B0601-2001, is preferably 2.0 μm or less, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, and particularly preferably 0.5 μm or less. Within such a range, the thickness of the resin laminate can be made thinner. The lower limit of the ten-point average roughness Rzjis of the surface of the metal foil facing the resin laminate is not particularly limited, but from the viewpoint of improving adhesion with the resin laminate, Rzjis is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.05 μm or more.

[0038] The thickness of the metal foil is not particularly limited, but is preferably 0.1 μm or more and 100 μm or less, more preferably 0.5 μm or more and 70 μm or less, even more preferably 2 μm or more and 70 μm or less, particularly preferably 10 μm or more and 70 μm or less, and most preferably 10 μm or more and 35 μm or less. If the thickness is within these ranges, a general pattern formation method for forming wiring on a printed wiring board, such as the MSAP (modified semi-additive) method, the SAP (semi-additive) method, and the subtractive method, can be adopted. However, when the thickness of the metal foil is, for example, 10 μm or less, the resin-coated metal foil of the present invention may be a carrier-coated metal foil having a release layer and a carrier and a resin laminate formed on the metal foil surface to improve handling.

[0039] Dielectric Layer The resin laminate of the present invention is preferably cured to form a dielectric layer. That is, according to a preferred embodiment of the present invention, a dielectric layer is provided that includes the resin laminate of the present invention and has the first and second resin compositions cured. The resin composition may be cured based on a known method, but is preferably cured by hot vacuum pressing. The thickness of the dielectric layer is not particularly limited as long as the desired capacitance can be secured, but is preferably 0.2 μm or more and 30 μm or less, more preferably 0.5 μm or more and 20 μm or less, particularly preferably 1 μm or more and 10 μm or less, and most preferably 2 μm or more and 6 μm or less. If the thickness is within these ranges, there are advantages such as easy realization of high capacitance, easy formation of a resin laminate by application of the resin composition, easy securing of sufficient adhesion with the metal foil, and easy obtaining of stable interlayer insulation.

[0040] Capacitor element and capacitor-embedded printed wiring board The resin laminate of the present invention or a dielectric layer containing the same is preferably incorporated into a capacitor element. That is, according to a preferred embodiment of the present invention, a capacitor element having the above-mentioned dielectric layer is provided. The configuration of the capacitor element is not particularly limited, and a known configuration can be adopted. A particularly preferred embodiment is a capacitor-embedded printed wiring board in which a capacitor or its dielectric layer is incorporated as an inner layer part of a printed wiring board. That is, according to a particularly preferred embodiment of the present invention, a capacitor-embedded printed wiring board having the above-mentioned dielectric layer is provided. In particular, by using the resin-coated metal foil of the present invention, a capacitor element or a capacitor-embedded printed wiring board can be efficiently manufactured based on a known method. EXAMPLES

[0041] The present invention will now be further illustrated by the following examples.

[0042] Example 1 (1) Preparation of resin varnish First, the resin components and imidazole-based curing accelerator shown below were prepared as raw material components for a resin varnish. - Epoxy resin: DIC Corporation, 850-S (bisphenol A type, epoxy equivalent 188g / Eq) - Diamine compound: Wakayama Seika Kogyo Co., Ltd., BAPP (2,2-bis[4-(4-aminophenoxy)phenyl]propane, active hydrogen group equivalent 102g / Eq) - Polyimide resin: Arakawa Chemical Industries, Ltd., PIAD-300 (terminal functional group: carboxyl group, solvent: mixture of cyclohexanone, methylcyclohexane and ethylene glycol dimethyl ether) - Imidazole curing accelerator: Shikoku Chemical Industry Co., Ltd., 2P4MHZ, (2-phenyl-4-methyl-5-hydroxymethylimidazole, added amount 1.0wt% relative to 100wt% of resin component)

[0043] Two types of resin varnishes, one for the first resin composition and one for the second resin composition, were prepared as follows. The raw material components for the resin varnish were weighed out in the mixing ratio (weight ratio) shown in Table 1. Then, cyclopentanone solvent was weighed out, and the raw material components for the resin varnish and the cyclopentanone solvent were charged into a flask and stirred at 60°C. After confirming that there was no residual raw material in the resin varnish and that the resin varnish was transparent, the resin varnish was collected.

[0044] (2) Mixing with filler Next, the following dielectric fillers and dispersants were prepared. - Dielectric filler: BaTiO3, manufactured by Nippon Chemical Industry Co., Ltd., AKBT-S (average particle size D measured by laser diffraction scattering particle size distribution measurement) 50 =0.3μm) - Dispersant: Titanate-based coupling agent, KR-44 manufactured by Ajinomoto Fine-Techno Co., Ltd. (1.5 parts by weight added per 100 parts by weight of dielectric filler)

[0045] To prepare each of the first resin composition and the second resin composition, the cyclopentanone solvent, the dielectric filler, and the dispersant were weighed out. The weighed out solvent, the dielectric filler, and the dispersant were slurried in a disperser. After the slurrying was confirmed, the resin varnish for the first resin composition or the second resin composition was weighed out so that the final dielectric filler had the compounding ratio (weight ratio) shown in Table 1, and was kneaded with the dielectric filler-containing slurry in a disperser. It was confirmed that the dielectric filler was not aggregated after kneading. In this way, a coating liquid containing the first resin composition and a coating liquid containing the second resin composition were obtained.

[0046] (3) Resin coating As shown in Fig. 3, the first resin composition was applied to a copper foil 16 (manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 18 µm, surface roughness Rzjis = 0.5 µm) using a bar coater so that the thickness of the first layer 12 after drying would be 2.0 µm, and then it was dried for 3 minutes in an oven heated to 130°C to semi-cure the resin. In this way, a first resin-coated copper foil 20 was obtained.

[0047] 3, the second resin composition was applied to a copper foil 16' (manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 18 μm, surface roughness Rzjis=0.5 μm) using a bar coater so that the thickness of the second layer 14 after drying would be 2.0 μm, and then it was dried for 3 minutes in an oven heated to 130° C. to semi-cure the resin. In this way, a second resin-coated copper foil 22 was obtained.

[0048] (4) Press As shown in FIG. 3, the first resin-coated copper foil 20 and the second resin-coated copper foil 22 were laminated so that their resin-coated surfaces faced each other, and the laminate was subjected to a pressure of 40 kgf / cm 2 The first and second resin compositions were cured by vacuum pressing at 200° C. for 90 minutes. A metal-clad laminate 30 was obtained that contained the resin laminate 10 made of the cured first and second resin compositions as a dielectric layer, and the dielectric layer used a copper foil with a thickness of 4.0 μm.

[0049] (5) Circuit formation and evaluation One side of the obtained metal-clad laminate 30 was etched to form a circuit 32 for various evaluations, and the following various evaluations were carried out.

[0050] <Evaluation 1: Peel strength (circuit adhesion)> One side of the metal-clad laminate 30 was etched to form a 3 mm wide linear circuit 32, and the circuit 32 was then peeled off at a peeling speed of 50 mm / min using an autograph to measure the peel strength. This measurement was performed in accordance with IPC-TM-650 2.4.8. The measured peel strength was evaluated according to the following criteria. The results are shown in Table 1. - Rating AA: 0.7kgf / cm or higher (best) - Rating A: 0.6kgf / cm or more and less than 0.7kgf / cm (good) - Rating B: 0.4kgf / cm or more and less than 0.6kgf / cm (acceptable) - Rating C: Less than 0.4kgf / cm (unacceptable)

[0051] <Evaluation 2: Capacitance (Cp)> One side of the metal-clad laminate 30 was etched to form a circular circuit with a diameter of 0.5 inches (12.6 mm), and the capacitance was measured at a frequency of 1 kHz using an LCR meter (HIOKI EE Corporation, LCR HiTester 3532-50). This measurement was performed in accordance with IPC-TM-650 2.5.2. The results are shown in Table 1. In the application of the present invention, a capacitance of 30 nF / in 2 This is particularly important since it is essential to have higher filter performance. - Rating AA: 50nF / in 2 Above (best) - Rating A: 40nF / in 2 or more and 50nF / in 2 Less than (good) - Rating B: 30nF / in 2 or more and 40nF / in 2 Less than (OK) - Rating C: 30nF / in 2 Less than (not acceptable)

[0052] <Evaluation 3: Dielectric breakdown voltage (BDV)> One side of the metal-clad laminate 30 was etched to form a circular circuit with a diameter of 0.5 inches (12.6 mm), and then the dielectric breakdown voltage was measured at a voltage rise rate of 80 V / sec using an insulation resistance tester (Super Insulation Meter SM7110, manufactured by Hioki E.E. Corporation). This measurement was performed in accordance with IPC-TM-650 2.5.6.2. The results are shown in Table 1. - Rating AA: 100V or more (best) - Rating A: 50V or more and less than 100V (good) - Rating B: 30V or more and less than 50V (acceptable) - Rating C: Less than 30V (not acceptable)

[0053] <Evaluation 4: Leakage current> One side of the metal-clad laminate 30 was etched to create a circular circuit with a diameter of 0.5 inches (12.6 mm), and the leakage current was measured under an applied voltage of 50 V using an insulation resistance tester (Super Insulation Meter SM7110, manufactured by Hioki E.E. Corporation). This measurement was performed in accordance with IPC-TM-650 2.5.7.2. The results are shown in Table 1. - Rating AA: Less than 10μA (best) - Rating A: 10μA or more and less than 30μA (good) - Rating B: 30μA or more and less than 50μA (acceptable) - Rating C: 50μA or more (not acceptable)

[0054] <Evaluation 5: Interlayer insulation (B-HAST)> Both sides of the metal-clad laminate 30 were etched to form a circular circuit with a diameter of 0.5 inches (12.6 mm), and then wiring was soldered to the upper and lower electrodes, and the wiring was connected to a migration measurement tester. The evaluation circuit was placed in a constant temperature and humidity chamber at 130°C and 85% RH, and a voltage of 3 V was applied between the upper and lower electrodes. At this time, a voltage of 1×10 5The time during which the insulation resistance of Ω or more was maintained was measured, and the transition of the insulation resistance value was observed. The measured interlayer insulation retention time and transition of the insulation resistance value were evaluated according to the following criteria. This measurement was performed in accordance with JESD22-A110. The results are shown in Table 1. - Rating AA: Maintained for 96 hours or more with no deterioration of insulation resistance (best) - Rating A: After 96 hours or more, deterioration of insulation resistance was observed (good) - Evaluation B: Retention for 48 hours or more but less than 96 hours (acceptable) - Rating C: Less than 48 hours (not acceptable)

[0055] <Overall rating> The overall evaluation was determined by applying the evaluation results of 1 to 5 to the following criteria. The results are shown in Table 1. - AA rating: AA or A rating in all ratings (best) - Rating A: There are no items rated C, but there is only one item rated B (good) - Rating B: There are no C grades, but there are two or more B grades (passable) - Rating C: At least one C rating (not acceptable)

[0056] Example 2 (comparison) A metal-clad laminate was produced and evaluated in the same manner as in Example 1, except that no second resin-coated copper foil 22 was used and two first resin-coated copper foils 20 were laminated with their coated resin surfaces facing each other.

[0057] Example 3 (comparison) A metal-clad laminate was produced and evaluated in the same manner as in Example 1, except that the first resin-coated copper foil 20 was not used and two second resin-coated copper foils 22 were laminated with their coated resin surfaces facing each other.

[0058] Examples 4 to 10 The metal-clad laminate was produced and evaluated in the same manner as in Example 1, except that in (1) above, the raw material components for the resin varnish were weighed out in the mixing ratio (weight ratio) shown in Table 2, in (3) above, the resin coating was performed as follows, and in (4) above, the pressing was performed as follows.

[0059] (3') Resin coating 5, the first resin composition was applied to a copper foil 16 (manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 18 μm, surface roughness Rzjis=0.5 μm) using a bar coater so that the thickness of the first layer 12 after drying would be 1.0 μm, and then it was dried for 3 minutes in an oven heated to 130° C. to semi-cure the resin. In this way, two first resin-coated copper foils 20 and 20′ were produced.

[0060] 5, the second resin composition was applied to the surface of the first layer 12 of the first resin-coated copper foil 20' using a bar coater so that the second layer 14 would have a thickness of 2.0 μm after drying, and then dried for 3 minutes in an oven heated to 130° C. to semi-cure the resin. In this way, a two-layer resin-coated copper foil 24' was obtained, which had the first layer 12 made of the first resin composition and the second layer 14 made of the second resin composition in that order on the copper foil 16'.

[0061] (4') Press As shown in FIG. 5, the first resin-coated copper foil 20 and the two-layer resin-coated copper foil 24' were laminated so that their resin-coated surfaces faced each other, and the laminate was subjected to a pressure of 40 kgf / cm 2 Then, the resin composition was vacuum pressed at 200°C for 90 minutes to cure the resin composition. A metal-clad laminate 30' was obtained, which included a resin laminate 10' made of the cured first and second resin compositions as a dielectric layer, and the dielectric layer had a thickness of 4.0 μm. The dielectric layer, which is the resin laminate 10' thus obtained, has a three-layer structure including, in order, a first layer 12 made of the first resin composition, a second layer 14 made of the second resin composition, and a first layer 12 made of the first resin composition.

[0062] Example 11 (comparison) In the above (3'), instead of coating the second resin composition on the surface of the first layer 12 of the first resin-coated copper foil 20', a polyimide film (Kapton (registered trademark), thickness 4 μm, manufactured by Toray DuPont Co., Ltd.) was laminated as the second layer 14 to produce a two-layer resin-coated copper foil 24'. A metal-clad laminate was produced and evaluated in the same manner as in Example 4, except that.

[0063] [Table 1]

[0064] [Table 2]

Claims

1. A resin laminate comprising a first layer made of a first resin composition and a second layer made of a second resin composition provided on one surface of the first layer, The first resin composition is A resin component including an epoxy resin, a diamine compound, and a polyimide resin; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 60 parts by weight or more and 85 parts by weight or less relative to 100 parts by weight of the solid content of the first resin composition; The content of the polyimide resin in the first resin composition is 20 parts by weight or more and 60 parts by weight or less with respect to 100 parts by weight of the resin component, The second resin composition is a resin component containing an epoxy resin and a diamine compound but not containing a polyimide resin; A dielectric filler which is a composite metal oxide containing at least two selected from the group consisting of Ba, Ti, Sr, Pb, Zr, La, Ta and Bi, in an amount of 70 parts by weight or more and 90 parts by weight or less relative to 100 parts by weight of the solid content of the second resin composition; A resin laminate comprising:

2. The resin laminate according to claim 1 , further comprising another first layer composed of the first resin composition on a surface of the second layer away from the first layer.

3. 3. The resin laminate according to claim 1, wherein the first resin composition has a total content of the epoxy resin and the diamine compound of 40 parts by weight or more and 80 parts by weight or less relative to 100 parts by weight of the resin component.

4. The resin laminate according to any one of claims 1 to 3, wherein the first resin composition has a content of the diamine compound in an amount such that, when the number of epoxy groups in the epoxy resin is taken as 1, the number of active hydrogen groups in the diamine compound is 0.5 or more and 1.5 or less.

5. The resin laminate according to any one of claims 1 to 3, wherein the first resin composition has a content of the diamine compound in an amount such that, when the number of epoxy groups in the epoxy resin is taken as 1, the number of active hydrogen groups in the diamine compound is 0.65 or more and 1.0 or less.

6. The composite metal oxide contained in the first resin composition is BaTiO 3 , SrTiO 3 , Pb(Zr,Ti)O 3 , PbLaTiO 3 , PbLaZrO, and SrBi 2 T 2 O 9 The resin laminate according to any one of claims 1 to 5, comprising at least one selected from the group consisting of:

7. The composite metal oxide contained in the first resin composition is BaTiO 3 The resin laminate according to any one of claims 1 to 6,

8. The resin laminate according to any one of claims 1 to 7, wherein the second resin composition has a content of the diamine compound in an amount such that, when the number of epoxy groups in the epoxy resin is taken as 1, the number of active hydrogen groups in the diamine compound is 0.5 or more and 1.5 or less.

9. The resin laminate according to any one of claims 1 to 7, wherein the second resin composition has a content of the diamine compound in an amount such that, when the number of epoxy groups in the epoxy resin is taken as 1, the number of active hydrogen groups in the diamine compound is 0.65 or more and 1.0 or less.

10. The composite metal oxide contained in the second resin composition is BaTiO 3 , SrTiO 3 , Pb(Zr,Ti)O 3 , PbLaTiO 3 , PbLaZrO, and SrBi 2 T 2 O 9 The resin laminate according to any one of claims 1 to 9, comprising at least one selected from the group consisting of:

11. The composite metal oxide contained in the second resin composition is BaTiO 3 The resin laminate according to any one of claims 1 to 10,

12. A dielectric layer comprising the resin laminate according to any one of claims 1 to 11, in which the first resin composition and the second resin composition are cured.

13. The dielectric layer according to claim 12, wherein the thickness of the dielectric layer is 0.2 μm or more and 30 μm or less.

14. A resin-coated metal foil comprising a metal foil and the resin laminate according to any one of claims 1 to 11 provided on at least one surface of the metal foil.

15. The resin-coated metal foil according to claim 14, wherein the metal foil is provided on both sides of the resin laminate.

16. The resin-coated metal foil according to claim 14 or 15, wherein the metal foil is a copper foil.

17. A capacitor element comprising the dielectric layer according to claim 12 or 13.

18. A printed wiring board with built-in capacitors, comprising the dielectric layer according to claim 12 or 13.

Citation Information

Patent Citations

  • Double-sided copper-clad laminate for forming capacitor layer and manufacturing method thereof

    JP2003039595A

  • Manufacturing method of capacitor layer forming material, and the material obtained by the method

    JP2006165400A

  • Resin composition for embedded capacitor which is excellent in adhesive force, heat resistance and flame retardance

    JP2006225653A

  • Prepreg, laminate, printed wiring board, coreless substrate, semiconductor package and method for manufacturing coreless substrate

    JP2018130938A

  • Thermosetting resin composition and use thereof

    WO2005080466A1